Hyper.Campus – Effects of Artificial Gravity on Structural and Functional Brain Plasticity During Head-Down Tilt Bed Rest - Stahn, Alexander; Dinges; Roalf, D.; Gur, R.C.; Brauns, K.; Werner, A.; Riecke, Bernhard E.; Wolbers, T.; Gunga, H.C.; Buchert, R.; Kühn, S.; Basner, M. (NASA Human Research Program IWS, 2019)
Gur
Keywords: NSERC DG 2026; Riecke_2019; alex-stahn; bernhard-riecke; posterWithoutPaper; talkWithoutPaper